Rivaroxaban in heart failure patients with left ventricular thrombus: A retrospective study - Zhang, Qian; Zhang, Zhongfan; Zheng, Haikuo; Qu, Ming; Li, Shouping; Yang, Ping; Si, Daoyuan; Zhang, Wenqi (Frontiers in Pharmacology, 2022)
Background: The role of rivaroxaban in patients with heart failure (HF) combined with left ventricular (LV) thrombus remains unknown in current guideline-directed anticoagulant therapy. The aim of this study was to investigate the impact of rivaroxaban versus vitamin K antagonists (VKAs) in patients with HF combined with LV thrombus. Methods: We retrospectively extracted clinical, echocardiographic and follow-up data of HF patients (all classifications) admitted at China-Japan Union Hospital of Jilin University from January 2017 to June 2021. A total of 198 patients with HF were identified with LV thrombus by echocardiography, 78 of them were managed with VKAs, 109 with rivaroxaban, and 11 with other antithrombotic regimens. Results: The median follow-up was 17.0 months (interquartile range: 6.0 to 24.0 months). High rates of major cardiovascular adverse events (MACEs) were observed in both the rivaroxaban and VKAs groups (49.5% vs. 57.7%). However, rivaroxaban versus VKAS observed a decrease in MACEs (adjusted HR:0.636; 95%CI:0.418-0.970; p=0.035) and systemic embolism (4.6% vs. 12.8%; adjusted HR:0.318; 95%CI:0.108-0.933; p=0.037; Gray’s test p=0.041) but was not found to have a benefit with regard to LV thrombus resolution (59.6% vs. 70.6%; adjusted HR: 1.303; 95% CI:0.898-1.890; p=0.163; Gray’s test p=0.073). Additionally, there was no significant between-group difference in the rate of International Society on Thrombosis and Hemostasis(ISTH) bleeding events. Conclusions: Our data found that in populations with HF combined with LV thrombus, the overall prognosis in both the rivaroxaban and VKAs groups was catastrophic. Although rivaroxaban improved the prognosis to some extent, a considerable need remains for new treatments to improve their clinical course.